UNDERSTANDING ENGLISH LANGUAGE TEACHERS’ VIEWS OF TEACHER RESEARCH: A REPORT FROM INDONESIA - Wulyani, Anik Nunuk; Saukah, Ali; Syahid, Abdul; Utami, IGA. Lokita Purnamika; Susilo, Susilo; Fiftinova, Fiftinova; Sukerti, Gusti Nyoman Ayu; Azis, Astuti; Amin, Muhammad (TEFLIN Journal, 2021)
This article reports on a study investigating the perceptions of EFL teachers in schools and language courses (henceforth, teachers) and EFL lecturers in tertiary educational institutions (academic staff) from Indonesia regarding their definitions of and their engagements in teacher research. An online questionnaire was used to gather quantitative data from almost 400 EFL teachers and academic staff from Indonesia. The questionnaire was followed by in-depth interviews with some respondents who met the criteria set and agreed to be interviewed. Results from the study show that both teachers and academic staff align research with evidence-based practice, survey, literature-driven practice and professional communication, and observation-based popular article. In terms of engagements, most of the teachers and academic staff read research papers occasionally, and more academic staff did research compared to teachers. Research done by both teachers and academic staff is largely associated with internal and external factors, such as, professional awareness and professional obligation, with academic staff seem to receive more support to engage in research. The findings of the study provide insights for future continuous professional development (CPD) activities for English teachers and academic staff. The activities might involve exploring ways to integrate teacher research into teachers’ and academic staff’s teaching responsibilities and integrating teacher research into the short-term and long-term goals of CPD.